Efektivitas Penerapan Buerger Allen Exercise terhadap Sensitivitas Kaki pada Penderita Diabetes Melitus di Kelurahan Pebatuan - Julia Nesti; Silvia Nora Anggreini (Jurnal Kesehatan Amanah, 2026)
Non-communicable diseases such as Diabetes Mellitus (DM) can lead to serious complications, including neuropathy and angiopathy caused by microvascular and macrovascular damage. These conditions impair peripheral blood circulation, resulting in decreased foot sensitivity characterized by cramps, tingling, cold extremities, and pale skin. If untreated, the risk of diabetic foot ulcers and amputation increases significantly. This study aimed to analyze the effectiveness of Buerger Allen Exercise in improving foot sensitivity and peripheral perfusion among DM patients in Pebatuan Village. A nursing care intervention focusing on ineffective peripheral perfusion was conducted on six respondents aged 45–60 years with random blood glucose levels above 200 mg/dL. The exercise was performed for 15–30 minutes, twice daily, over six consecutive days. Foot sensitivity was assessed using daily pre-test and post-test observations. The results showed an increase in sensitivity scores from 0–1 to 2 in all participants. Clinical improvements included reduced cramps and tingling, normalized skin color and extremity temperature, and improved capillary refill time (<3 seconds). Buerger Allen Exercise proved to be an effective, simple, and cost-free intervention for enhancing lower-extremity blood circulation, improving foot sensitivity, and preventing diabetic foot complications.